Assistance to Early Childhood Education Teachers in Developing a Curriculum Based on Local Wisdom in Tilatang Kamang District, Agam Regency - Hazizah, Nur; Pransiska, Rismareni; Anggraini, Vivi; Putri, Elssy Assari (Universitas Negeri Padang, 2024)
This service aims to assist teachers in developing an independent curriculum that integrates local wisdom in early childhood learning activities to make it more enjoyable in the Tilatang Kamang sub-district, Agam Regency. The method used is 1) creating a guidebook that can be used by PAUD teachers in developing the curriculum, the guide is equipped with identifying local local wisdom topics, integrating local wisdom-based topics into independent curriculum topics, teaching modules, lesson plans, and formats. assessments that can be used, 2) providing in-depth study of material related to local wisdom and the independent curriculum, 3) assisting teachers in developing more fun and innovative media and learning tools based on local wisdom, 4) assisting teachers in creating learning activities based on the Strengthening the Pancasila Student Profile Project ( P5) which is integrated into local wisdom. The results of the implementation of this assistance involved 20 TK/RA in Tilatang Kamang District with 21 representatives from each school. After participating in mentoring activities, it was seen that teachers already understood the development of an independent curriculum based on local wisdom. This was shown by an increase in teachers' understanding of integrating local culture into topics in the independent curriculum, creating teaching modules and lesson plans as well as implementing the Strengthening Pancasila Student Profile Project (P5 ) with more programmed and contextual activities.